TATA KELOLA TAMAN BACAAN MASYARAKAT “MELATI” DESA KOLAM SEBAGAI SARANA BELAJAR ANAK DI MASA COVID-19 - Wildansyah Lubis; Waliyul Maulana Siregar; Jubaidah Hasibuan; Lala Jelita Ananda (Universitas Negeri Medan, 2021)
At the beginning of the establishment of the reading park it was intended as a means of reading for the community, but due to the Covid-19 pandemic, the reading garden no longer functions as it used to, there was a decrease in visits by people who initially visited the reading garden a lot. Based on observations, the decrease in the interest of reading garden visitors was caused by several things, namely 1) the design of the reading park location was not well organized; 2) A collection of reading gardens that are less varied and not updated; 3) Social restrictions imposed during the Covid-19 pandemic; and 4) the lack of understanding of the management of the reading park (Community for the Children of the Pond Village and Karang Taruna) regarding the management of an attractive reading park and in accordance with health protocol standards during the Covid-19 pandemic. Therefore, based on this problem, a solution was agreed upon to provide strengthening of the governance of the community reading garden for the Children's Community in the Pool Village and the Karang Taruna in the Pool Village as the manager of the